Does Managerial Support Drive Employee Satisfaction? A Study of Branch Managers in the Insurance Sector (The International Research Journal of Management Science, 2025)
Purpose. This study assesses the impact of branch managers' leadership effectiveness on the job satisfaction of insurance employees in Nepal.Design/methodology/approach. The population comprised employees working under branch managers in insurance companies within Kathmandu Valley. Data were gathered from 211 respondents using a structured survey questionnaire via convenience sampling.Findings. Linear regression analysis revealed that effective leadership has a positive impact on job satisfaction (β = 0.82, p < 0.001), explaining 67.6 % of its variance. These findings underscore the vital role of effective leadership in enhancing employee satisfaction and, consequently, organizational productivity among insurance employees.Research implications. The study's implications are significant for management while emphasizing the necessity of examining leadership development programs to cultivate effective branch managers. Furthermore, it provides researchers with a validated model and instrument for measuring these constructs within the unique context of Nepal's insurance industry.Originality/value. This study provides original empirical evidence specifically addressing the critical gap in research on leadership and job satisfaction within Nepal's insurance sector. The findings offer practical value to industry management by quantifying the strong influence of branch-level leadership, highlighting a strategic factor for improving job satisfaction and organizational performance.